Contralateral stenosis and echolucent plaque morphology are associated with elevated stroke risk in patients treated with asymptomatic carotid artery stenosis within a controlled clinical trial (SPACE-2) - Reiff, Tilman; Eckstein, Hans-Henning; Mansmann, Ulrich; Jansen, Olav; Fraedrich, Gustav; Mudra, Harald; Böckler, Dittmar; Böhm, Michael; Brückmann, Hartmut; Debus, E. Sebastian; Fiehler, Jens; Mathias, Klaus; et al. (Journal of stroke and cerebrovascular diseases, 2021)
Background - Asymptomatic carotid artery stenosis (ACS) has a low risk of stroke. To achieve an advantage over noninterventional best medical treatment (BMT), carotid endarterectomy (CEA) or carotid artery stenting (CAS) must be performed with the lowest possible risk of stroke. Therefore, an analysis of risk-elevating factors is essential. Grade of ipsilateral and contralateral stenosis as well as plaque morphology are known risk factors in ACS. - Methods - The randomized, controlled, multicenter SPACE-2 trial had to be stopped prematurely after recruiting 513 patients. 203 patients were randomized to CEA, 197 to CAS, and 113 to BMT. Within one year, risk factors such as grade of stenosis and plaque morphology were analyzed. - Results - Grade of contralateral stenosis (GCS) was higher in patients with any stroke (50%ECST vs. 20%ECST; p=0.012). Echolucent plaque morphology was associated with any stroke on the day of intervention (OR 5.23; p=0.041). In the periprocedural period, any stroke was correlated with GCS in the CEA group (70%ECST vs. 20%ECST; p=0.026) and with echolucent plaque morphology in the CAS group (6% vs. 1%; p=0.048). In multivariate analysis, occlusion of the contralateral carotid artery (CCO) was associated with risk of any stroke (OR 7.00; p=0.006), without heterogeneity between CEA and CAS. - Conclusion - In patients with asymptomatic carotid artery stenosis, GCS, CCO, as well as echolucent plaque morphology were associated with a higher risk of cerebrovascular events. The risk of stroke in the periprocedural period was increased by GCS in CEA and by echolucent plaque in CAS. Due to small sample size, results must be interpreted carefully.
Collaborators: Pricipal investigations and further study personnel: Beyersdorf F, Möhlenbruch M [und viele weitere]
Gesehen am 05.11.2021